PEMANFAATAN LIMBAH BONGGOL JAGUNG DAN TULANG IKAN SEBAGAI SUPLEMEN KALSIUM (GO-CORI) UNTUK MENCEGAH HIPOKALSEMIA PADA TERNAK RUMINANSIA - DL, Amelia; Putri, Ade Widya; Lestari, Amelia Dwi; Prayoga, Putri Nanda; Prayitno, Syanly Hanan Al Sidan; Pawestri, Wari (Institute for Research and Community Services, 2024)
Hypocalcemia is a disease associated with the nutritional management of ruminant livestock, arising from insufficient calcium intake. The inadequate knowledge and capability of livestock farmers in meeting the nutritional requirements significantly contribute to the occurrence of this condition. Addressing the nutritional needs of livestock can be achieved through supplemental interventions. Parmelina, et al. Pemanfaatan Limbah Bonggol Jagung dan Tulang Ikan Sebagai Suplemen Kalsium (GO-CORI) untuk Mencegah Hipokalsemia pada Ternak Ruminansia Copyright © 2024 Parmelina, et al. Published by Institute for Research and Community Service, Atma Jaya Catholic University of Indonesia. This articles is licensed under a Creative Common Attribution-NonCommercial-Share Alike 4.0 International License. 103 GO-CORI mineral blocks serve as a livestock supplement tailored to meet the nutritional demands of ruminant animals, aiming to prevent hypocalcemia. GO-CORI innovates by utilizing corn cob waste and fish bones as raw materials for its production. Laboratory tests confirm that GO-CORI contains high levels of calcium. The qualitative methodology employed encompasses preimplementation, implementation, and post-implementation phases. The abundance of corn cob waste and fish bones, along with their high calcium content, adds substantial value to the product. Being environmentally friendly and rich in calcium content. GO-CORI presents substantial market potential, positioning itself for competitive standing among similar products.